THE IMPLEMENTATION OF FASTING FIDYAH ACCORDING TO IMAM SYAFI’I IN PAYA GELI VILLAGE OF SUNGGAL DISTRICT DELI SERDANG - Zainal Arifin; Muhammad Aqsha; Muhammad Fauzi Lubis (Universitas Dharmawangsa Medan, 2020)
But there’s a scripture deduction in Al- Baqarah (184) : Meaning : “And upon those who are able (to fast, but with hardship) a ransom ( as suitable) offeeding a poor person (each day).” This verse explained that Rukhsah was given byAllah for certain person. Study of fasting fidyah according to Imam Syafi”i are: (a)senile person cause Elderly; (b) a prolonged illness that can’t possibly cure, (c).Pregnant and nursing woman who are worried for their children. (d) died person andhave a fasting load that wasn’t on Qada in his lifetime.